Post-Pandemic Asia A New Normal for Regional Security? - Berkofsky, Axel (ISPI Publications, 2021)
In 2020, the way we define "insecurity" has drastically changed. Insecurity can now also be invisible and all around us, in the shape of a virus that disrupts people's lives, upends the economy, subverts the core functions of national governments and jeopardises the foundations of international cooperation. At the same time, the SARS-CoV-2 pandemic has not made traditional security challenges disappear, especially in and around Asia. This Report presents short- and long-term scenarios for each of the hotspots that challenge peace and stability in Asia, a region that, after the pandemic, has become even more crucial for a swift global recovery.